2011
DOI: 10.1073/pnas.1106556108
|View full text |Cite
|
Sign up to set email alerts
|

Control of body size by oxygen supply reveals size-dependent and size-independent mechanisms of molting and metamorphosis

Abstract: Body size profoundly affects many aspects of animal biology, including metamorphosis, allometry, size-dependent alternative pathways of gene expression, and the social and ecological roles of individuals. However, regulation of body size is one of the fundamental unsolved problems in developmental biology. The control of body size requires a mechanism that assesses size and stops growth within a characteristic range of sizes. Under normal growth conditions in Manduca sexta, the endocrine cascade that causes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
247
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(274 citation statements)
references
References 33 publications
23
247
0
Order By: Relevance
“…Recently, an additional regulator of critical size has been proposed-oxygen level [51]. In all holometabolous insects, tracheal volume is largely fixed within an instar and only expands at each larval moult.…”
Section: (A) Regulation Of Critical Sizementioning
confidence: 99%
“…Recently, an additional regulator of critical size has been proposed-oxygen level [51]. In all holometabolous insects, tracheal volume is largely fixed within an instar and only expands at each larval moult.…”
Section: (A) Regulation Of Critical Sizementioning
confidence: 99%
“…For example, the hormone ecdysone has been shown to be a secreted signal important for the timing of larval stage transitions in the moth Manduca sexta. Ecdysone is secreted at a precisely controlled critical size threshold, which prepares the moth for metamorphosis [16]. If larvae have not reached the critical size due to low food availability, they will undergo additional growth phases and intercalary moults until they have achieved the required size for the metamorphic moult [17].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism responsible for size detection in insects has been well elaborated in only a small number of species. Among these species it has been variously found that commitment to moulting is triggered by abdominal stretch receptors [37], the exhaustion of a prepackaged food supply [38], or size-imposed oxygen limitation [39]. More recently it has been found that nutritional condition may better describe the process of moulting [40][41][42].…”
Section: Discussionmentioning
confidence: 99%